Speak or shut up: that is the question for nurses (Research, Society and Development, 2021)
Introduction: The way how inter-professional relationships in health are established can generate errors and harm to patients. Objective: examine the nurses' ability to manifest themselves in the face of failures in patient care with the potential for adverse events; and, identify facilitators capable of enhancing the voice of nurses, in the face of ongoing unsafe acts, practiced by health professionals in two hospitals in the metropolitan region of Porto Alegre / RS. Methodology: a multiple and embedded case study was carried out. Data collection between July and August 2020, through semi-structured, virtual, and recorded interviews; for data analysis, the method of analysis of Laurence Bardin was adopted. Results: the ability of nurses to express their concerns related to patient safety depended on some factors in addition to the severity of the damage, such as the personal aspect, the person to be challenged or questioned, the professional (where, approaching the medical team was more difficult than the nursing technician), and the situation or context. Speech enhancers also emerged, mainly: personnel, experience, knowledge, leadership, management, and processes. Conclusion: personal characteristics, such as maturity, and knowledge, helped in decision making, while interdisciplinarity appeared discreetly in the speeches, reinforcing the need for teamwork with this focus, in order to share knowledge and support in uncertainties.